2016
DOI: 10.1007/s00266-016-0681-2
|View full text |Cite
|
Sign up to set email alerts
|

Massive Cerebral Infarction Following Facial Fat Injection

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the A5 online Instructions to Authors www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Having the same clinical symptoms, with a highlight over the neurological features and no traumatic involvement, fat embolism syndrome could be expressed as a cerebral fat embolism, the latter one being able to worsen the prognostic of the patients. Nevertheless, in a cerebral fat embolism, neurological manifestation may mask respiratory symptoms or they may even be absent, making diagnosis challenging [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Having the same clinical symptoms, with a highlight over the neurological features and no traumatic involvement, fat embolism syndrome could be expressed as a cerebral fat embolism, the latter one being able to worsen the prognostic of the patients. Nevertheless, in a cerebral fat embolism, neurological manifestation may mask respiratory symptoms or they may even be absent, making diagnosis challenging [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Fat injection into the face is occasionally associated with complications when fat enters facial arteries and subsequently orbital and cerebral arteries, causing vision loss or cerebral infarction . Yoon et al reported a case of acute fatal stroke following autologous fat injection to the face.…”
Section: Discussionmentioning
confidence: 99%
“…Fat grafting does carry a risk of intra-luminal injection causing necrosis and infarct of the end organ tissue, which in the head and neck can be devastating and there are numerous reports of blindness, facial skin loss, fat embolic syndrome and cerebral infarct (37)(38)(39).…”
Section: Risks Of Autologous Fat Graftingmentioning
confidence: 99%